CYP1A1, smoking and venous thromboembolism - Zhu, Jin; Zheng, Wen-Jie; Kong, Fan-Cui; Zhang, Wei-Juan; Wang, He-Yao; Wang, Chen (Thrombosis and Haemostasis, 2010)
Since CYP1A1 enzyme is involved in metabolism of tobacco carcinogens, the CYP1A1 gene may be of relevance to smoking-induced differences in the risks of venous thromboembolism (VTE). We conducted a case-control study to investigate genetic polymorphisms in CYP1A1 that might modify the risk of developing VTE. A total of 425 Chinese patients with VTE and 527 VTE-free control individuals, matched by age and gender, were included in this analysis. The MspI and Ile462Val polymorphisms in CYP1A1 gene were analysed using the Amplification Refractory Mutation System (ARMS) method. The Ile462Val AG variant and combined AG and GG variant was significantly associated with VTE, adjusted for age, gender, weight and contraceptives (OR=1.362, 95%CI 1.026, 1.809, p=0.033; OR=1.420, 95% CI 1.081, 1.865, p=0.012, respectively); The AG and GG combined variant was still significantly associated with VTE when adjusting further for smoking (OR=1.344, 95%CI 1.019,1.772, p=0.036) A more than two-fold increase for VTE was associated with the Ile462Val combined variant of AG+GG (OR of 2.805, 95% CI 1.250, 6.293, p=0.012) in the smokers. Genetic variations of CYP1A1 Ile462Val contribute to susceptibility to smoking-induced VTE in the Chinese populations. A two-fold increase in the risk in the smokers in the patients who carry CYP1A1 Ile462Val variant alleles has demonstrated the importance of gene-environment interactions in the development of this disease.
Keywords: CYP1A1; smoking; venous thromboembolism; ARMS; Chinese